2016
DOI: 10.1007/s10664-015-9424-2
|View full text |Cite
|
Sign up to set email alerts
|

A detailed investigation of the effectiveness of whole test suite generation

Abstract: A common application of search-based software testing is to generate test cases for all goals defined by a coverage criterion (e.g., lines, branches, mutants). Rather than generating one test case at a time for each of these goals individually, whole test suite generation optimizes entire test suites towards satisfying all goals at the same time. There is evidence that the overall coverage achieved with this approach is superior to that of targeting individual coverage goals. Nevertheless, there remains some u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 28 publications
0
72
0
Order By: Relevance
“…We selected this benchmark since it has been widely used in the literature to assess test case generation tools [18], [51], [48]. However, Shamshiri et al [51] showed that the vast majority of classes in the FS110 corpus are trivial to cover fully, even with random search algorithms.…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…We selected this benchmark since it has been widely used in the literature to assess test case generation tools [18], [51], [48]. However, Shamshiri et al [51] showed that the vast majority of classes in the FS110 corpus are trivial to cover fully, even with random search algorithms.…”
Section: Subjectsmentioning
confidence: 99%
“…Recently, Rojas et al [48] developed the Whole Suite with Archive approach (WSA), a hybrid strategy that incorporates some of MOSA's routines inside the traditional WS approach. While WSA still applies the sum scalarization and works at the test suite level, it incorporates an archive strategy which operates at the test case level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whole test suite generation. Whole test suite generation builds an entire test suite by simultaneously optimizing multiple fitness functions (e.g., for multiple coverage criteria) [34], [35]. In principle and with appropriate fitness functions defined for validity and representativeness, the problem addressed in this paper can be formulated as whole test suite generation.…”
Section: Related Workmentioning
confidence: 99%
“…The more coverage they TS will achieve the better chance will the contracts have of capturing errors. It is therefore proposed to use Whole Test Suite Generation instead of proposed to use Whole Test Suite (WTS) [5] Generation instead of randomly generation to create the initial TS for AutoInfer. WTS is the state of the art that uses the genetic Algorithm (GA) to generate the entire TS evolutionally at the same time.…”
Section: Introductionmentioning
confidence: 99%